Keberlanjutan Program Pekarangan Pangan Lestari Anggota Kelompok Wanita Tani di Provinsi Lampung - Novrianty, Ely; Rangga, Kordiyana K; Listiana, Indah; Gitosaputro, Sumaryo; Syarief, Yuniar Aviati (Fakultas Pertanian, Universitas Lampung, 2023)
ABSTRACT Development engaged in the food sector is one of the country's needs in increasing production and meeting needs, especially food. The Sustainable Food Yard Program (P2L) is one of the programs that is expected to be able to provide an increase in food production, especially for family consumption needs. The purpose of this study was to analyze the factors that influence the sustainability of the sustainable food garden program of women farmer groups in Lampung Province. The research method used is a quantitative method. The population in this study are members of the women's farmer group and stakeholders (stakeholders). Respondents studied amounted to 85 people. Data collection was carried out in June 2022. The data analysis method used was linear logistic regression analysis to determine the factors that influence program sustainability. The results showed that the level of sustainability of sustainable food gardens in Lampung Province was influenced by internal and external factors. Formal education, non-formal education, cosmopolitan level, number of family dependents, infrastructure, government support, market institutions and village nurseries and product marketing influence the level of sustainability of P2L in Lampung Province. Suggestions in this study are expected by certain parties, especially stakeholders and the government to be able to provide a forum and education for farmer women's groups in increasing knowledge and skills in managing and developing P2L programs. Keywords: farmer women's group, sustainable food yard, sustainability